Translation Techniques in Translating Children's Bilingual Storybooks - Maharani, Clara Yudith (Universitas Sebelas Maret, 2025)
Bilingual children's storybooks are a medium to learn English. This study focused on the translation process from previous studies. This study employs a descriptive qualitative method. The purpose of this study is to find the frequently used translation techniques, strategies, and procedures in studies of translating children's bilingual storybooks. This study found that the most frequently used translation technique is literal translation. Furthermore, the word-for-word is commonly used by the translator.